Interface Interaction Dependent Growth of Carbon Nanostructures: An In Situ Study. Issue 19 (6th May 2022) - Zhang, Xiaofang; Tian, Dongliang; Yang, Feng; Zhao, Haofei; Lau, Woon‐Ming; Wang, Rongming
Abstract: Controllable synthesis of carbon nanostructures is expected to achieve high electrical, optical, and mechanical performance for various applications. Despite great progress in this field, controllable synthesis of carbon nanostructures, i.e., graphite shells (GSs) and carbon nanotubes (CNTs), is still demanded to be deeply revealed. Here, a strategy is demonstrated to achieve GSs and bamboo CNTs by regulating the interface interaction via in situ pyrolysis of Co phthalocyanine (CoPc) in an environmental transmission electron microscopy (ETEM) at atomic resolution. The results indicate that the catalyst involves the nucleation, combination, and reconstruction of Co/Co3 C, the growth modes of the carbon, i.e., base‐growth or tip‐growth, and nanostructures are dependent on the interface interaction between catalyst and substrate controlled by temperature. High temperature favors tip‐growth of bamboo CNTs with larger catalyst nanoparticles (NPs) (≈20 nm), while low temperature favors the base‐growth of GSs with smaller NPs (≈10 nm). The average growth rate of 131.3 nm s −1 at 850 °C is about 60 times compared with that at 750 °C. The work provides a comprehensive understanding of distinct growth mode of GSs and CNTs at different temperatures, which would be valuable for the controllable growth of carbon nanostructures by catalyst design and engineering. Abstract : Controllable growth of graphite shells (GSs) and bamboo carbon nanotubes (CNTs) has been demonstrated by adjusting interface interaction between catalyst and substrate via temperature, and its growth mechanism has been revealed via in situ pyrolysis of Co phthalocyanine (CoPc) in an aberration‐corrected environmental transmission electron microscopy (ETEM).